2021
DOI: 10.3390/ijms22115948
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered sgsh Mutant Zebrafish Recapitulates Molecular and Behavioural Pathobiology of Sanfilippo Syndrome A/MPS IIIA

Abstract: Mucopolysaccharidosis IIIA (MPS IIIA, Sanfilippo syndrome type A), a paediatric neurological lysosomal storage disease, is caused by impaired function of the enzyme N-sulfoglucosamine sulfohydrolase (SGSH) resulting in impaired catabolism of heparan sulfate glycosaminoglycan (HS GAG) and its accumulation in tissues. MPS IIIA represents a significant proportion of childhood dementias. This condition generally leads to patient death in the teenage years, yet no effective therapy exists for MPS IIIA and a complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 107 publications
(150 reference statements)
2
14
0
Order By: Relevance
“…The arena was divided into two areas, inner and outer, of equivalent surface, and thigmotaxis was presented as the percentage of the total distance moved or the total time spent by each larva into the outer zone (Figure 8d). Our measurements showed that there is no significant difference in thigmotaxis behavior between eed −/− mutants and wild-type larvae Thigmotaxis (or "wall hugging") is a common behavioral endpoint used in preclinical studies employing rodents but also applied to the zebrafish model [74,75]. Animals engaged in thigmotaxic behavior strongly avoid the center of an arena and reduce their exploration behavior to stay or move in close proximity to the boundaries of the environ-ment.…”
Section: Loss Of Eed Function Alters Locomotor Activitymentioning
confidence: 79%
See 1 more Smart Citation
“…The arena was divided into two areas, inner and outer, of equivalent surface, and thigmotaxis was presented as the percentage of the total distance moved or the total time spent by each larva into the outer zone (Figure 8d). Our measurements showed that there is no significant difference in thigmotaxis behavior between eed −/− mutants and wild-type larvae Thigmotaxis (or "wall hugging") is a common behavioral endpoint used in preclinical studies employing rodents but also applied to the zebrafish model [74,75]. Animals engaged in thigmotaxic behavior strongly avoid the center of an arena and reduce their exploration behavior to stay or move in close proximity to the boundaries of the environ-ment.…”
Section: Loss Of Eed Function Alters Locomotor Activitymentioning
confidence: 79%
“…This hyperactive phenotype of eed −/− mutant is particularly prominent and significant during the dark cycles (Figure 8b,c). Thigmotaxis (or "wall hugging") is a common behavioral endpoint used in preclinical studies employing rodents but also applied to the zebrafish model [74,75]. Animals engaged in thigmotaxic behavior strongly avoid the center of an arena and reduce their exploration behavior to stay or move in close proximity to the boundaries of the environment.…”
Section: Loss Of Eed Function Alters Locomotor Activitymentioning
confidence: 99%
“…Despite this, it remains unclear how this manifests as the characteristic progressive functional neurodegeneration observed in MPS patients. Several studies have implicated multiple factors contributing to disease progression, including microgliosis and neuroinflammation 1,8,42 , CNS atrophy 43 , and more recently an increasing recognition of the role of functional synaptic impairments [44][45][46] . However, most studies have looked at these features largely in isolation; here, we have performed the first transcriptomic and proteomic characterisation of the CNS of an animal model of MPS IIIA, the sgsh zebrafish 8 , with the aim of globally determining the features associated with disease progression and defining the diverse cellular and molecular perturbations that accumulate in the MPS IIIA brain.…”
Section: Discussionmentioning
confidence: 99%
“… Abstract Mucopolysaccharidoses are lysosomal storage diseases that collectively represent a major cause of lethal, treatment-refractory childhood dementias 17 Clinically-useful interventions are hampered due to an incomplete understanding of their neuropathological origins. Using the zebrafish sgsh model of mucopolysaccharidosis IIIA 8 (MPS IIIA, Sanfilippo syndrome A), we conducted several ‘omics-based analyses, and developed and benchmarked a novel bioinformatic feature classification and ranking model for high-throughput datasets – ExIR – to prioritise important features in the progression of neurological manifestations of the disease. We find that the massive endolysosomal burden resulting from increased lysosomal storage of heparan sulfate and other secondarily accumulating substrates, such as sphingolipids, induces abnormal microtubule organisation and vesicle trafficking in neurons.…”
mentioning
confidence: 99%
“…Recently, Douek et al [ 24 ] generated a sgsh Δex5−6 zebrafish mutant by CRISPR/Cas9 to study MPS IIIA and found that it exhibited central nervous system (CNS)-specific defective features, including neuronal lysosomal overabundance, complex behavioral phenotypes, and neuroinflammation. They also found that the pharmacological inhibition of Caspase-1 could partially rescue the behavioral abnormality that occurred in sgsh Δex5−6 mutant larvae.…”
Section: Introductionmentioning
confidence: 99%